PHYSIOTHERAPY MANAGEMENT OF PHASE II REHABILITATION POST ANTERIOR CRUCIATE LIGAMENT (ACL) RECONSTRUCTION: OPTIMIZATION OF MUSCLE STRENGTH AND RANGE OF MOTION OF THE KNEE JOINT - Khoirunnisa'; Wijianto; Halim Mardianto (CV. Fahr Publishing, 2026)
Anterior cruciate ligament (ACL) injury is one of the most common knee ligament injuries among physically active adolescents, particularly in sports requiring frequent pivoting and landing such as basketball. Functional outcomes following ACL reconstruction are strongly influenced by the quality of postoperative physiotherapy, especially during Phase II rehabilitation, which serves as a transition toward higher functional activities. This study aimed to evaluate the outcomes of Phase II physiotherapy management incorporating progressive weight-bearing exercises on muscle strength, knee range of motion, pain, and functional performance in an adolescent patient after ACL reconstruction. A case report design was applied to a 17-year-old female patient following anterior cruciate ligament reconstruction (ACLR). The intervention program consisted of progressive strengthening exercises (mini squats and lunges), balance and stability training, range of motion exercises, and functional task-oriented training. Outcome measures included muscle strength assessed using a sphygmomanometer, knee range of motion measured with a goniometer, pain intensity evaluated using the Visual Analogue Scale (VAS), and functional performance assessed using the Lysholm Knee Scoring Scale (LKSS). The results demonstrated improvements in quadriceps strength (145–210 mmHg) and hamstring strength (130–155 mmHg), restoration of full knee extension (−5° to 0°), increased knee flexion to 145°, decreased pain intensity (VAS 4 to VAS 1), and improved functional performance (LKSS 79 to 92). Phase II physiotherapy incorporating progressive weight-bearing exercises resulted in clinically meaningful improvements in knee function and prepared the patient for advanced rehabilitation phases.